Krumme tæer: Skam i krydsfeltet mellem queer, feministiske og postkoloniale teorier - Mons Bissenbakker Frederiksen (The Royal Danish Library, 2013)
Squirming perspectives. Shame in the intersection of queer, feminist, and postcolonial theories gives a critical introduction to the ways in which queer theories have recently turned to the concept of shame. Taking my starting point in Tomkins and Sedgwick, I show why queer theorists have suggested shame as an essential part of subject formation as well as a possible strategy for queer resistance. However, I also present a range of important (primarily postcolonial and crip theoretical) criticisms that have been raised against the queer celebration of shame and its presumed universal qualities. Turning to Sara Ahmed’s phenomenological investigations of shame as a performative phenomenon, I suggest the critical investigation of the effects of such universalisations as the more pressing question for queer shame theories.